2019
DOI: 10.1017/dsi.2019.313
|View full text |Cite
|
Sign up to set email alerts
|

How are End-of-Life Strategies Adopted in Product-Service Systems? A Systematic Review of General Cases and Cases of Medical Devices Industry

Abstract: Little study has been done on the adoption of End-of-Life (EoL) strategies on the medical devices industry, despite the reasons why it is an important area of study for the implementation of circularity. The rates of waste in the medical field are alarming and tend to grow. Though presenting a wide potential for EoL strategies implementation, the medical field is also inherently challenging, considering the rigid regulations and product's risk to patients life. This paper analyses 17 Product-Service System cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…medical devices/equipment) presented a reduced number of possible patterns, which might be associated to difficulties for diversification of CEBMs. These observations are consistent with previous research (Damha et al, 2019;Schröter and Lay, 2014) that also identified limitations or specific patterns for servitisation in the medical devices/equipment sector due to regulatory restrictions or strong influence of few actors in the value chain (e.g. public hospitals and insurance companies).…”
Section: Key Insightssupporting
confidence: 92%
“…medical devices/equipment) presented a reduced number of possible patterns, which might be associated to difficulties for diversification of CEBMs. These observations are consistent with previous research (Damha et al, 2019;Schröter and Lay, 2014) that also identified limitations or specific patterns for servitisation in the medical devices/equipment sector due to regulatory restrictions or strong influence of few actors in the value chain (e.g. public hospitals and insurance companies).…”
Section: Key Insightssupporting
confidence: 92%
“…The 9R's has been proposed as a more comprehensive and integrated structure for circularity (Okorie et al, 2018). In line with Damha et al (2019), the SLR's unit of analysis was empirical studies already published in the literature. In this case, a paper can present more than one case to be examined.…”
Section: Data Collectionmentioning
confidence: 99%
“…In detail, the development process is the most impactful, as many prototypes are produced and, after meeting regulatory requirements and passing rigorous qualification phases, only a handful are released on the market [44]. Accordingly, this sector presents great potential for the implementation of end-of-life (EoL) approaches aimed at improving the environmental performances of the overall equipment life cycle and putting into practice circular economy strategies [45]. Increasing the reuse, refurbishment, and remanufacturing options can, together with a proper maintenance service, allow the transition from a single life cycle to a multiple product life cycles approach [46].…”
Section: Overviewmentioning
confidence: 99%